2022
DOI: 10.1021/acsami.2c09008
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band, Efficient Self-Powered Organic Photodetectors with Isotype Subphthalocyanine-Based Heterojunctions toward Secure Optical Communications

Abstract: High-performance heterojunction organic photodetectors (OPDs) are of great significance in optical detecting technology due to their tailorable optoelectronic properties. Herein, we designed and synthesized three n-type subphthalocyanine (SubPc) derivatives PhO-BSubPcF12, CHO-PhO-BSubPcF12, and NO2-PhO-BSubPcF12 via axial nonhalogen substitution on fluorinated SubPc. These SubPc derivatives exhibit improved intramolecular charge transfer, high electron mobilities, optimized energy levels, and good thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…[9,[23][24][25][26] However, it remains a challenge in developing a photodetector with dual-band response. Previous solutions usually focused on the multi-stacked photosensitive layers (heterojunction stacking or single semiconductor stacking), dependent on the photosensitive layers with different spectral response band to realize dual-band response in a single photodetector, [27][28][29][30][31] further, most of them required assistant of bidirectional charge injection. Moreover, spectral matching and interfaces contacting in the multi-stacked structure complex the device fabrication process.…”
mentioning
confidence: 99%
“…[9,[23][24][25][26] However, it remains a challenge in developing a photodetector with dual-band response. Previous solutions usually focused on the multi-stacked photosensitive layers (heterojunction stacking or single semiconductor stacking), dependent on the photosensitive layers with different spectral response band to realize dual-band response in a single photodetector, [27][28][29][30][31] further, most of them required assistant of bidirectional charge injection. Moreover, spectral matching and interfaces contacting in the multi-stacked structure complex the device fabrication process.…”
mentioning
confidence: 99%
“…In addition, the linear dynamic range (LDR), which is an advantage value of the PDs and represents a strong range of light intensity with a constant response rate, is another index to evaluate the PDs. This parameter can be defined as follows normalL normalD normalR .25em ( d B ) = 20 log nobreak0em.25em⁡ I normalp normalh I normald normala normalr normalk …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Figure 4d,e reveals that the highest detectivity (D*) and EQE of the device are 6 × 10 10 Jones and 273%, which are comparable to or even better than the previous reported 4H-SiC-based PDs (as summarized shown in Table 1). In addition, the linear dynamic range (LDR), which is an advantage value of the PDs and represents a strong range of light intensity with a constant response rate, 40 is another index to evaluate the This parameter can be defined as follows 41 = I I LDR (dB) 20log ph dark (8) Figure 4f shows the LDR curve of the SiC PD exposed to different light intensities. It is observed that the LDR of the PD is responsive over a wide range of light intensities and gradually increases as the light intensity increases, and it reaches a maximum value of 48 dB at 35.60 mW/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the resulting device showed low performance with an EQE value of 10.9% and a detectivity of 5 Â 10 10 Jones at a bias voltage of 0 V. 39 Lan et al used a PHJ of the Br-BSubPc/NO 2 -PhO-BSubPcF 12 layer, which can achieve a low dark current density of 9.2 Â 10 À10 A cm À2 but a low EQE of 30.6% at a bias voltage of 0 V. Thus, the detectivity at a wavelength of 570 nm shows the value of 8.19 Â 10 12 Jones. 40 Shen et al demonstrated that PHJ organic photodetectors based on the fullerene acceptor using SubPc/C 60 as an active layer can achieve an EQE of 40.6% and a dark current density of 1.2 Â 10 À7 A cm À2 , which results in detectivity with a value of 1.7 Â 10 À11 Jones. 41 Regardless of limitations in exciton diffusion length, BHJ shows a charge-trapping effect and efficient exciton dissociation.…”
Section: Introductionmentioning
confidence: 99%